PROFESIONALISME GURU MENIGKATKAN CITRA DUNIA PENDIDIKAN - Syahril Chaniago (Jurnal Ilmiah Econosains, 2013)
Abstract The teacher is a person who is authorized and responsible to guide and nurture students, either individually or in groups class and outside of class. Teachers as educators are professionals in charge of planning, implementing the learning process, and assess learning outcomes as well as coaching and training to students. A fact that must be accepted that the teacher is not akhi-final first-class citizens, but citizens with disabilities. It is well known, the presence of the teacher, not by design but by condition. Teacher is not a pure ideal situation but for various reasons, so it often appears related news is inappropriate teacher behavior. Perhaps this is one reason teachers do not have the character and personality of the teacher should be, certainly more dim the image of the teaching profession. Self-image as an educator would ease concerns the admissibility of properly by the environment. Personality is a dynamic organization of sitem pshikhofisik determines a unique adjustment to the environment. Personality is an inner state of a person that determines how he looks in adjusting to the environment. There are several factors that determine the development of the personality, which include: actor innate, environmental factors, and the interaction of innate and environmental. One of the life skills that teachers should have the ability to constantly develop and maintain self-image as an educator. Self-image as an educator would ease concerns the admissibility of teachers with good attendance by the environment. Furthermore, it is very influential to the trust will be given to the task of educating teachers. As an educator, teacher in daily life are required to always have the self-awareness that mandated profession. The figure of the teacher should be able to personally set an example for students and the environment. Their behavior will always be the public highlights. Keywords: Teacher Character, Personality and Image of the Teaching Profession